Produção financeira das autorizações de internação hospitalar no Hospital Geral de Roraima - Rocha, Bruno Miranda da (2013)
Public health in Brazil is inserted in a historical context quite complex in what refers the financing of services. The various forms of financing that has been created, changed and recreated, generate many questions about its efficiency and applicability. The Ministry of Health currently works the mode financing in five blocks to fund the benefit SUS: Basic Attention; Attention of Average and Alta Complexity Ambulatorial and Hospitalar; Surveillance in Health; Pharmaceutical Assistance; SUS Management. The activities assistential performed in regime of hospitalization, by public services and Private that integrate the Sistema Único de Health, are borne by means the system of financing hospital, having as operational instrument the Hospital Information System of System Unified Health (SIH / SUS) and your form own, the Authorization of Hospitalization (AIH). The Objective this research is contribute to the knowledge of health financing in Roraima, to from the study of question in Hospital Geral de Roraima, particularly in what refers to resources used in procedures of medium and high complexity. Searching-if thus, do a lifting of Commitments of Hospitalization, checking the volume of resources implicated, well as the means by which these procedures are financed. How result we verified that the number of AIH disallowed is signifier getting close of 10% of total AIH processed in first four months of 2012. The main reasons of disallowance were lack of cadastre of many professionals in the system CNES (Nacional Cadastre of Health Establishments) and the CBO (Brasilian Occupations Cadastre) of professionals incompatible with the procedure performed. Being thus became evident a management problem to reduce the numbers AIH disallowed in HGR-RR and so contribute to a better health financing in Roraima.